Wacana kolonial dalam film "Moeder Dao, de schildpadgelijkende" - Soegiarto, Jugiarie (Wacana, Journal of the Humanities of Indonesia, 2008)
Documentary maker Vincent Monnikendam compiled the film Mother Dao, the turtlelike (1995) from more than 200 titles of archived films of the Dutch-Indies, shot between 1912 to ca. 1933. This film is neither a remake nor an edited version, but a kind of collage from those hundreds of archival films, all were silent. Monnikendam re-arranged the images and provided them with a new sound frame, consisting of songs, chantings and poems, in Indonesian, Old Javanese, and Sundanese. This new composition is not just creative but also quite provocative. With this arrangement the cineast wanted to show that there was something not quite right with colonialism. Through the new composition of images and the sound framing we can observe the power relation between the colonizer and the colonized. There are contrasts between the colonial and the colonized, literally as well as metaphorically. These contrasts raised some questions about the colonial discourse.